2014
DOI: 10.1039/c4md00081a
|View full text |Cite
|
Sign up to set email alerts
|

When proteins start to make sense: fine-tuning of aminoglycosides for PTC suppression therapy

Abstract: Aminoglycosides (AGs) are highly potent antibacterial agents, which are known to exert their deleterious effects on bacterial cells by interfering with the translation process, leading to aberrant protein synthesis that usually results in cell death. Nearly 45 years ago, AGs were shown to induce read-through activity in prokaryotic systems by selectively encoding tRNA molecules at premature termination codon (PTC) positions; resulting in the generation of full length functional proteins. However, only in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 114 publications
(225 reference statements)
1
48
0
Order By: Relevance
“…This can been achieved with the use of the nonsense-codon suppressors Ataluren, read-through compound (RTC)13, Amlexanox, synthetic aminoglycosides and nonaminoglycosides (Du et al, 2008(Du et al, , 2009Gonzalez-Hilarion et al, 2012;Nakamura et al, 2012;Shalev and Baasov, 2014;Welch et al, 2007), although their lack of drug-target specificity is a great concern, given the large number of physiological cellular mRNAs that are NMD targets. Among these compounds, Ataluren (Translarna) is farthest along the drug-development pipeline, as it has shown the greatest effectiveness in treating Duchenne muscular dystrophy caused by nonsense mutations, but at doses that do not detectably inhibit NMD, consistent with its mild effects on cellular metabolism (Finkel et al, 2013;Welch et al, 2007).…”
Section: Therapeutic Approaches For Ptc-associated Diseasesmentioning
confidence: 99%
“…This can been achieved with the use of the nonsense-codon suppressors Ataluren, read-through compound (RTC)13, Amlexanox, synthetic aminoglycosides and nonaminoglycosides (Du et al, 2008(Du et al, , 2009Gonzalez-Hilarion et al, 2012;Nakamura et al, 2012;Shalev and Baasov, 2014;Welch et al, 2007), although their lack of drug-target specificity is a great concern, given the large number of physiological cellular mRNAs that are NMD targets. Among these compounds, Ataluren (Translarna) is farthest along the drug-development pipeline, as it has shown the greatest effectiveness in treating Duchenne muscular dystrophy caused by nonsense mutations, but at doses that do not detectably inhibit NMD, consistent with its mild effects on cellular metabolism (Finkel et al, 2013;Welch et al, 2007).…”
Section: Therapeutic Approaches For Ptc-associated Diseasesmentioning
confidence: 99%
“…8-10 , translocation 2,3,11,12 , and ribosome recycling 8 and by inducing translational miscoding 2-4,13 through specific interactions with the decoding site (A-site) of the 16S ribosomal RNA (rRNA) in helix 44 (h44) of the small (30S) ribosomal subunit 14-17 (Figure 1b), and in the case of some aminoglycosides, with helix 69 (H69) of the large (50S) ribosomal subunit. 8,10,12,15,18 Aminoglycosides also show promise as treatments for other diseases, including HIV 2 ; human genetic disorders, where their ability to induce miscoding has been used to suppress disease-associated premature termination codons 2,19 ; and fungal infection, where amphiphilic aminoglycoside analogs have been shown to perturb the function of the fungal plasma membrane. 20 …”
mentioning
confidence: 99%
“…1B). We chose the TGA codon over the other two stop codons because evidence from previous studies indicated that UGA in mRNA exhibits the highest rate of read-through (15)(16)(17)21). Neoresistant HEK293 cells were cotransfected with CMV-loxP-NeoloxP-DsRed2, along with Pgk-nsCre plasmids with stop codons inserted into one of the two positions.…”
Section: Significancementioning
confidence: 99%
“…In the absence of any intervention, the majority of PTC-containing mRNAs is rapidly degraded by the process of nonsense-mediated decay (NMD), whereas only a small fraction of the transcripts can be translated into truncated, nonfunctional peptides (13). Aminoglycosides, such as gentamycin and geneticin (G418), protect mutant transcripts from NMD and promote read-through of PTCs (14)(15)(16). This process, termed nonsense suppression, has been shown to restore synthesis of full-length, functional proteins in numerous cell culture assays, animal models of human diseases, and even in patients with DMD or CF (17)(18)(19).…”
mentioning
confidence: 99%